European disintegration? Euroscepticism and Europe's rural/urban divide. Issue 3 (27th May 2019) - Schoene, Matthew
ABSTRACT: Euroscepticism has been a persistent part of the European integration process over the last several decades (Usherwood and Startin [2013]. Euroscepticism as a persistent phenomenon. JCMS: Journal of Common Market Studies, 51, 1–16). Scholars have proposed various theories to explain resistance to integration by drawing upon economic, political and cultural theories. In this paper, I ask whether Euroscepticism is a by-product of rural–urban divisions, which influences one's perception of the economy, one's trust of transnational politics and one's cultural identity. However, geographical variables have never been tested in the presence of these more well-established Euroscepticism predictors. Here, I use the European Social Survey to compare the predictive power of economic, political, cultural and geographical variables on two forms of Euroscepticism: trust in European Parliament and the belief that integration has gone too far. Multilevel mixed-effects regression models demonstrate that trust in the European Parliament is indeed higher in big cities, but overall, place of residence is not a strong predictor of Euroscepticism. Among other theories, I find that cultural variables are more meaningful than economics or politics. I finally conclude with a discussion of the EU's future.